Occupational Health di Sektor Pendidikan Indonesia: Sebuah Studi Literatur - Candra Indraswari (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to review the existing literature on the existing literature on the implementation of occupational health in the Indonesian education sector and identify the challenges associated with its implementation within school environments. The study employs a literature review approach by examining scholarly journal articles, academic books, international organizational guidelines, and national policy documents published between 2020 and 2026. The literature was retrieved from major academic databases, including Google Scholar, ScienceDirect, SpringerLink, Taylor & Francis, and PubMed, as well as official publications issued by the World Health Organization (WHO), the International Labour Organization (ILO), the Ministry of Health of the Republic of Indonesia, and the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. The findings indicate that the education sector is exposed to a wide range of occupational health risks, including ergonomic, biological, psychosocial, and physical environmental hazards, as well as excessive administrative workloads. Furthermore, the implementation of occupational health in schools continues to face several challenges, including limited policy support, inadequate awareness and understanding of occupational health principles, insufficient integration of health programs into school management systems, and suboptimal health monitoring mechanisms for teachers and educational personnel.